2012
DOI: 10.4319/lo.2012.57.3.0727
|View full text |Cite
|
Sign up to set email alerts
|

Grazing resistance allows bloom formation and may explain invasion success of Gonyostomum semen

Abstract: The nuisance alga Gonyostomum semen (Raphidophyceae) has expanded in the Nordic countries during the last decades and can dominate lake phytoplankton communities almost completely. A possible explanation to its dominance could be limited grazing by zooplankton. We investigated the potential grazing pressure on G. semen using an experimental approach supported by field data. We determined the grazing rate by cladocerans, calanoid copepods, and Chaoborus larvae to determine which were able to feed on G. semen. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 39 publications
(54 reference statements)
0
50
2
Order By: Relevance
“…It is therefore likely that both temperature and other factors are controlling the growth and inhibiting success of G. semen. Previous studies suggest that the presence of and grazing from certain zooplankton might influence the occurrence and growth success of G. semen (Hansson, 1996;Findlay et al, 2005;Lebret et al, 2012a;Johansson et al, 2013b), However, we did not have data for this in our study.…”
Section: Changes In Biomassmentioning
confidence: 71%
See 1 more Smart Citation
“…It is therefore likely that both temperature and other factors are controlling the growth and inhibiting success of G. semen. Previous studies suggest that the presence of and grazing from certain zooplankton might influence the occurrence and growth success of G. semen (Hansson, 1996;Findlay et al, 2005;Lebret et al, 2012a;Johansson et al, 2013b), However, we did not have data for this in our study.…”
Section: Changes In Biomassmentioning
confidence: 71%
“…During bloom periods, lower biomass of zooplankton food resources are observed (such as small chrysophytes and chlorophytes) and the assembly of zooplankton taxa differ between bloom and non-bloom lakes (Johansson et al, 2013a). Only some species of zooplankton are known to feed on G. semen ( Lebret et al, 2012a;Johansson et al, 2013b), and negative correlations are found both between large biomasses of G. semen and the amount of certain zooplankton grazers such as Daphnia (Bjørndalen, 1982;Findlay et al, 2005) and between Daphnia and G. semen recruitment rate from cysts (Hansson, 1996). Also G. semen causes problems when sampling with nets, caused by the slime ejected from the trichocysts at cell disturbance, and drinking waters may be affected by clogging of filters (Bjørnd-alen, 1982;Hongve et al, 1988;Berge, 1991;).…”
Section: Introductionmentioning
confidence: 99%
“…There was a supposition that due to its large size and presence of trichocysts the alga is inedible (Havens, 1989;Lebret et al 2012) but some researchers suggested that large zooplankton species may have a negative effect on alga abundance (Cronberg et al, 1988;Findlay et al, 2005). Two experimental studies (Lebret et al, 2012;Johansson et al, 2013) proved that some large species (like Daphnia magna and Eudiaptomus gracilis) could feed on the alga. Together with the fact that G. semen cyst recruitment is inhibited by the presence of Cladocera (Hansson, 2000) it is possible that the structure of zooplankton in lakes plays a role in the alga bloom forming.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is able to produce toxins, which can inhibit the development of other algae (Cronberg et al 1988;Reynolds 2006). The large size of cells and grazing avoidance strategies hamper the zooplankton pressure and favours the abundant occurrence of G. semen in brown water lakes (Rengefors et al 2008;Lebret et al 2012;Johansson et al 2013).…”
Section: Discussionmentioning
confidence: 99%